Rapid Apparent Diffusion Coefficient Evolution After Early Revascularization: A Potential Marker of Secondary Injury?. Issue 8 (August 2019) - Hsia, Amie W.; Luby, Marie; Cullison, Kaylie; Burton, Shannon; Armonda, Rocco; Liu, Ai-Hsi; Leigh, Richard; Nadareishvili, Zurab; Benson, Richard T.; Lynch, John K.; Latour, Lawrence L.
Abstract : Background and Purpose—: In this era of endovascular therapy (EVT) with early, complete recanalization and reperfusion, we have observed an even more rapid apparent diffusion coefficient (ADC) normalization within the acute ischemic lesion compared with the natural history or IV-tPA-treated patient. In this study, we aimed to evaluate the effect of revascularization on ADC evolution within the core lesion in the first 24 hours in acute ischemic stroke patients. Methods—: This retrospective study included anterior circulation acute ischemic stroke patients treated with EVT with or without intravenous tPA (IVT) from 2015 to 2017 compared with a consecutive cohort of IVT-only patients treated before 2015. Diffusion-weighted imaging and ADC maps were used to quantify baseline core lesions. Median ADC value change and core reversal were determined at 24 hours. Diffusion-weighted imaging lesion growth was measured at 24 hours and 5 days. Good clinical outcome was defined as modified Rankin Scale score of 0 to 2 at 90 days. Results—: Twenty-five patients (50%) received IVT while the other 25 patients received EVT (50%) with or without IVT. Between these patient groups, there were no differences in age, sex, baseline National Institutes of Health Stroke Scale, interhospital transfer, or IVT rates. Thirty-two patients (64%) revascularized with 69% receiving EVT. There was a significant increase in median ADC value of the core lesion at 24 hours in patients who revascularized compared with further ADC reduction in nonrevascularization patients. Revascularization patients had a significantly higher rate of good clinical outcome at 90 days, 63% versus 9% ( P =0.003). Core reversal at 24 hours was significantly higher in revascularization patients, 69% versus 22% ( P =0.002). Conclusions—: ADC evolution in acute ischemic stroke patients with early, complete revascularization, now more commonly seen with EVT, is strikingly different from our historical understanding. The early ADC normalization we have observed in this setting may include a component of secondary injury and serve as a potential imaging biomarker for the development of future adjunctive therapies. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00009243. Abstract : Supplemental Digital Content is available in the text.